DEVELOPMENT OF CONTROVERSIAL ISSUES-BASED STUDENT WORKSHEET TO IMPROVE STUDENT’S SOCIAL SKILL CLASS IV IN ELEMENTARY SCHOOL - Agung Bintoro; Alben Ambarita; Pargito Pargito (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to obtain decent controversial issues-based student worksheet or commonly known as LKPD and to understand the effectiveness ratio of student worksheet to improving of student’s social skills class IV in elementary school. The study method used is research and development in accordance with the theory of Borg & Gall. Collecting data utilizes social skill observation sheet. The subject to this research is students of class IV in elementary school. The results of the study show that the first, controversial issues-based student worksheet is appropriate to use. According to results of assessment, comment, and suggestion from the validation sheet which has been filled out by the validator, its category is